Descriptive study of tumbler user behavior to support green market development - Widi Sriwahyuni Pasaribu; Surmida Sormin; Zulfa Hazimah (International Journal of Applied Finance and Business Studies, 2025)
The environmental impact of plastic waste is extremely significant. Because plastic can take centuries to break down, it poses serious risks to wildlife, harms marine habitats, and can negatively affect human health. Growing global concern about this issue has encouraged people to switch to more ecofriendly products, while also creating opportunities for businesses to adapt their strategies to be more sustainable. This study employs a descriptive approach to examine the behavior of individuals using tumblers as eco-friendly products especially Gen Z , utilizing cross-tabulation techniques with SPSS software. The objective is to analyze the relationship between respondent profiles and their eco-friendly product usage. Data and descriptions regarding tumbler users in Medan City provide valuable insights for companies in the green entrepreneurship sector. The findings indicate that potential green consumers are predominantly female, aged 17-20, and currently students. Their primary motivation for choosing stainless steel tumblers is economic and practical considerations, followed by environmental awareness. These results offer a reference for green companies in the design and development of eco-friendly products and green marketing in particular.